The burden of hospital-acquired infections and antibiotic resistance in Bangladesh: current trends and policy implications - Zubair Zujbe; Nowshin Tabassum; Golam Kibria; Ahsan Ahmed; Mohammed Mehadi Hassan Chowdhury; Mohammad Sorowar Hossain (Discover Public Health)
Abstract Hospital-acquired infections (HAIs) and antimicrobial resistance (AMR) have emerged as significant public health concerns in Bangladesh and developing countries. This narrative study has highlighted the current scenario of AMR and HAIs in Bangladesh, thoroughly discussing the causes and recommended preventive measures aligned with the One Health global approach and antibiotic stewardship strategies. In this narrative review study, several potential factors were identified that caused the significant incidence of HAIs in Bangladesh, including poor hospital hygiene, crowded environment, lack of trained healthcare staff, ineffective environmental management system in hospitals, and insufficient monitoring. The key factors driving antibiotic resistance include the irrational prescription of antibiotics, limited awareness of antibiotic usage, the absence of infection control practices, and inadequate hygiene in many healthcare facilities. Therefore, this study suggested several comprehensive measures, including implementing the one health approach and antibiotic stewardship, enforcing antibiotic guidelines, and improving Infection prevention and control measures to combat AMR and HAIs.